2021
DOI: 10.1177/00315125211060231
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Based Interventions Aimed at Improving Balance in Children with Autism Spectrum Disorder: A Meta-Analysis

Abstract: Children with Autism Spectrum Disorder (ASD) often have deficits in motor skills, especially balance. This article presents a meta-analytic review of 15 intervention studies that aimed to improve balance in children and adolescents with ASD. Across these studies, there were 195 participants with ASD for whom pre-intervention and post-intervention balance scores were available. We measured the standardized mean difference (Hedges’ g) between their pre-intervention and post-intervention balance scores and found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 84 publications
2
8
0
Order By: Relevance
“…The meta-analysis demonstrates that exercise intervention has a moderate positive effect on SS (SMD = 0.73), which is similar to previous results ( 64 ). Balance is the ability of an individual to maintain a specific state of the body under dynamic, static, or kinesthetic conditions ( 65 ).…”
Section: Discussionsupporting
confidence: 90%
“…The meta-analysis demonstrates that exercise intervention has a moderate positive effect on SS (SMD = 0.73), which is similar to previous results ( 64 ). Balance is the ability of an individual to maintain a specific state of the body under dynamic, static, or kinesthetic conditions ( 65 ).…”
Section: Discussionsupporting
confidence: 90%
“…Our systematic review critically appraises the literature to date on the effects of PA/exercise interventions in young adults with ASD between 19 and 30 years. Most previous reviews have assessed the effects of PA/exercise interventions in children with ASD (Bodnar et al, 2020; Chan et al, 2021; Djordjević et al, 2022; Doreswamy et al, 2020; Flori & Angeli, 2021; Healy et al, 2019; Huang et al, 2020; Liang et al, 2022; Ruggeri et al, 2020; Teh et al, 2021; Vetri & Roccella, 2020). These reviews suggested positive effects of PA interventions on motor performance, autism severity, as well as social communication, behavioral, and cognitive skills.…”
Section: Introductionmentioning
confidence: 99%
“…These reviews suggested positive effects of PA interventions on motor performance, autism severity, as well as social communication, behavioral, and cognitive skills. For example, a meta-analysis of 15 exercise-based interventions involving 195 children with ASD up to 18 years of age suggested a large positive effect of the training on balance skills of children (Djordjević et al, 2022). In terms of effects outside the motor system, there is promising evidence from 12 clinical trials involving 350 children for improvements of small-to-medium size in communication and social functioning skills, both of which are core ASD impairments, following PA interventions (Chan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Autism spectrum disorder is a term used to describe a group of symptoms that include early-onset social communication deficits and repetitive sensory-motor behavior, as well as a strong genetic component and other factors (Djordjevi", Memisevic, Potic, & Djuric, 2021). Symptoms of autism spectrum disorder (ASD) usually appear in the first 3 years of life (Raj & Masood, 2020).…”
Section: Discussionmentioning
confidence: 99%